Novos monômeros obtidos a partir do metacrilato de glicidila, bisfenol A e 4, 4 isopropilidenodicicloexanol : síntese, caracterização estrutural e propriedades de compósitos para utilização em resinas de restauração dental - Reis, Jeanne Hemetério Cordeiro dos (2006)
Nowadays, composite resins are the direct restorative materials more important in dental clinical performance, due to their versatility and aesthetic excellence. Bis-GMA (2,2-bis[4(2-hydroxy-3-metacryloxypropoxy)phenil]propane) is the base monomer more frequently used in restorative composite resins. However, this monomer presents some disadvantages, such as high viscosity and two aromatic rings in its structure that can promote allergic reactions to the humans. In this work, the main purpose was to synthesize new monomers from glycidyl methacrylate to use in dental restorative materials. Structural characterization of the monomers was carried out through FTIR and NMR 1H, and eight composites were produced from the new monomers, by addition of silane-treated alumino silicate particles (inorganic filler) and a photocuring system (camphorquinone and ethyl 4-dimethylaminebenzoate). The composites were analyzed by environmental scanning electronic microscopy and the water sorption and solubility, compressive strength and elastic modulus were determined. A commercial composite resin [Z100 (3M)] was used to comparison effect. The new composites presented general characteristics similar to the commercial ones; however, they didn t present the properties expected. This behavior was attributed to the lower degree of monomer reaction and to the granulometry and size distribution of the mineral filler in the polymeric matrix